ANALISIS STRUKTUR DENGAN DINDING PENGISI DAN TANPA DINDING PENGISI PADA GEDUNG BERTINGKAT TERHADAP PERILAKU DINAMIK DENGAN METODE TIME HISTORY - CAHAYA, TIARA; Islam, Mukhlis; Afrizal, Yuzuar; Wahyuni, Ade Sri; Gunawan, Agustin (Universitas Bengkulu, 2023)
This study aims to compare structural modeling with the addition of wall elements and without walls with the help of SAP2000 software. The method used in this study is time history analysis using the San Fernando groundmotion data. Based on the modeling that has been done, the participation of the variance mass has reached 90% for structures with walls in mode 278 while without walls in mode 243. The addition of walls in this study resulted in a decrease in the drift value. The average percentage of settlement of each floor is 40.12% for the X direction and 30.26% for the Y direction. The addition of walls can also reduce the period value of the structure, where the structure with walls has a period value of 1.0804 seconds while the structure without walls is 1 ,2016 sec. Keywords: Building Structure, Infill Wall, Drift, Time History Analysis